Composite separator, method for preparing the same, and sodium-ion battery
Patent Information
- Application Number
- CN202611340269.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]本申请的主要目的在于提供一种复合隔膜及其制备方法和钠离子电池,以解决现有技术中的隔膜电解液浸润性差、热稳定性不足以及热压后易开口的问题
[0027]本申请提供的一种复合隔膜,复合隔膜包括基膜以及在基膜一侧涂布的胶层,胶层材料包括PVDF和PMMA,并且PVDF和PMMA的质量比为(90~60):(10~40)。利用胶层中PVDF和PMMA相互协同,形成具有较高模量的网络结构,不仅能够使胶层与基膜紧密粘结,增强复合隔膜的结构稳定性和机械强度,提高热稳定性,而且能够改善复合隔膜与电解液的浸润性,降低接触角,提高复合隔膜对电解液的吸液率,提高离子传输效率。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of sodium-ion battery technology, specifically to a composite separator, its preparation method, and a sodium-ion battery. Background Technology
[0002] Sodium-ion batteries have become an important alternative to lithium-ion batteries due to the abundance and low cost of sodium resources. As a key component of the battery, the separator needs to possess good ion conductivity, electronic insulation, mechanical strength, and thermal stability. Currently, commercially available separators are mainly made of polyolefins (PP / PE), but they suffer from problems such as poor electrolyte wettability, insufficient thermal stability, and easy opening after hot pressing.
[0003] Especially for sodium-ion batteries, which operate at higher voltages (often above 4.0V) and have stronger positive electrode oxidation, the separator needs to have superior oxidation resistance. PP (polypropylene), due to its regular molecular structure and high crystallinity, has better oxidation resistance than PE. It also has a higher membrane breakage temperature, better resisting the risk of short circuits at high temperatures. Its mechanical strength, puncture resistance, and tensile strength are all superior to PE, making it less prone to deformation and damage during manufacturing. It also exhibits better chemical stability to the electrolyte, improving battery yield and long-term reliability, but its wettability with the electrolyte is poor. PE (polyethylene) has a low closed-cell temperature, allowing for instantaneous thermal shutdown in case of thermal runaway, and good wettability, but its thermal stability is poor (melting point approximately 135°C). A PP / PE / PP three-layer composite separator can combine the oxidation resistance and high melting point of PP with the thermal shutdown characteristics of PE, but it still suffers from high rebound stress and a tendency to open after hot pressing.
[0004] To improve membrane performance, surface treatments such as ceramic coatings (e.g., Al2O3, boehmite) or polymer coatings (e.g., PVDF) are commonly used. Ceramic coatings have the disadvantages of high cost and low energy density; polymer coatings such as PVDF (polyvinylidene fluoride) have excellent electrochemical stability and adhesion, but the PVDF adhesive layer has insufficient modulus after hot pressing, making it difficult to resist the rebound stress of the PP base film, resulting in poor cell interface contact and reduced cycle life.
[0005] In view of the above, this application is hereby submitted. Summary of the Invention
[0006] The main objective of this application is to provide a composite separator, its preparation method, and a sodium-ion battery to solve the problems of poor electrolyte wettability, insufficient thermal stability, and easy opening after hot pressing in the prior art.
[0007] To achieve the above objectives, according to the first aspect of this application, a composite membrane is provided, the composite membrane comprising a base membrane, wherein an adhesive layer is coated on one side of the base membrane, the adhesive layer being made of PVDF and PMMA, and the mass ratio of the two being (90~60):(10~40).
[0008] Furthermore, the base film includes a first PP layer, a PE layer, and a second PP layer stacked sequentially, with a total thickness of 12μm to 20μm, and the thickness of the PE layer accounting for 30% to 40% of the total thickness of the base film.
[0009] Furthermore, the porosity of the base membrane is 40%~50%.
[0010] Furthermore, the thickness of the adhesive layer is 3μm~5μm.
[0011] To achieve the above objectives, according to a second aspect of this application, a method for preparing a composite separator is provided, comprising:
[0012] Step S1: Disperse PVDF and PMMA in an organic solvent to form a gel; wherein the mass ratio of PVDF to PMMA is (90~60):(10~40).
[0013] Step S2: Provide a base film, apply the adhesive solution to one side of the base film, dry to remove the organic solvent, and obtain a composite membrane with the adhesive layer attached to one side of the base film.
[0014] Furthermore, in step S1, the solid content of the adhesive is 10%~20%.
[0015] Furthermore, the organic solvent is N-methylpyrrolidone.
[0016] Further, in step S2, the adhesive is applied to one side of the base film by spraying.
[0017] Furthermore, the drying temperature is 30~120℃.
[0018] Furthermore, the method for preparing the base film in step S2 includes:
[0019] Step A1: The first PP masterbatch, PE masterbatch, and second PP masterbatch are co-extruded and cast to form a three-layer composite film; wherein, in the three-layer composite film, the first PP layer, PE layer, and second PP layer are stacked sequentially.
[0020] Step A2: Simultaneously biaxially stretch and shape the three-layer composite film to obtain the base film.
[0021] Further, step A2, biaxial stretching and setting, includes: longitudinal stretching, transverse stretching, and heat setting performed sequentially; wherein: the preheating temperature for longitudinal stretching is 125~135℃, the longitudinal stretching temperature is 125~140℃, and the longitudinal stretching ratio is 4~5 times; the preheating temperature for transverse stretching is 125~135℃, the transverse stretching temperature is 125~145℃, and the transverse stretching ratio is 4~5 times; the heat setting temperature is 150~160℃, and the relaxation rate of heat setting is 2%~5%.
[0022] According to a third aspect of this application, a sodium-ion battery is provided, the sodium-ion battery including a separator, the separator being a composite separator provided in the first aspect of this application or a composite separator obtained by the preparation method provided in the second aspect of this application.
[0023] Furthermore, sodium-ion batteries also include a positive electrode and a negative electrode, with the positive electrode comprising a positive active material.
[0024] Furthermore, the positive electrode active material is Na 0.98 Ni 0.33 Fe 0.33 Mn 0.33 O2.
[0025] Furthermore, the negative electrode sheet includes a negative electrode active material.
[0026] Furthermore, the negative electrode active material is hard carbon.
[0027] This application provides a composite separator, comprising a base membrane and an adhesive layer coated on one side of the base membrane. The adhesive layer material comprises PVDF and PMMA, and the mass ratio of PVDF to PMMA is (90~60):(10~40). By utilizing the synergistic interaction of PVDF and PMMA in the adhesive layer to form a network structure with high modulus, not only can the adhesive layer be tightly bonded to the base membrane, enhancing the structural stability and mechanical strength of the composite separator and improving thermal stability, but it can also improve the wettability of the composite separator with the electrolyte, reduce the contact angle, increase the electrolyte absorption rate of the composite separator, and improve ion transport efficiency.
[0028] Furthermore, the composite separator provided in this application utilizes the high-modulus network structure formed by PVDF and PMMA in the adhesive layer to effectively suppress the rebound stress of the base film during hot pressing, ensuring tight contact at the cell interface, preventing hot pressing opening, and thus extending the cycle life of the battery.
[0029] Therefore, by adjusting the mass ratio of PVDF and PMMA in the adhesive layer, the thermal stability, electrolyte wettability, and mechanical strength of the composite separator can be balanced, making the composite separator of this application suitable for sodium-ion batteries that require long cycle life, and it is also inexpensive, which is beneficial to the industrial production of sodium-ion batteries. Detailed Implementation
[0030] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present application will now be described in detail with reference to the embodiments.
[0031] Notes to English abbreviations appearing in this application:
[0032] PVDF: Polyvinylidene fluoride, possessing excellent electrochemical stability and adhesive properties; commercially available, such as Solef. ® 5130, with a molecular weight of approximately 1.1 million;
[0033] PMMA: Polymethyl methacrylate, is polar and commercially available. It has a particle size of 5μm and can be purchased from companies such as Gaorui GP-R75C, Haodian SW709, and Haofei HSA-4280.
[0034] PE: Polyethylene, with a low closed-cell temperature; PP: Polypropylene, with a regular molecular structure and high crystallinity.
[0035] As described in the background section of this application, existing technologies suffer from problems such as poor electrolyte wettability of the separator, insufficient thermal stability, and easy opening after hot pressing. To address these issues, this application provides a composite separator, its preparation method, and a sodium-ion battery.
[0036] In a first typical embodiment of this application, a composite diaphragm is provided, which includes a base membrane and an adhesive layer coated on one side of the base membrane. The adhesive layer is made of PVDF and PMMA, and the mass ratio of the two is (90~60):(10~40).
[0037] PVDF, a polymer with high electrochemical stability and good adhesion, can form a stable adhesive layer with the base membrane, enhancing the overall structural stability and mechanical strength of the separator. It also maintains the integrity of the separator under high-temperature conditions, thus improving thermal stability. The introduction of PMMA, due to its high polarity and good interfacial compatibility, significantly improves the wettability of the adhesive layer and electrolyte, reduces the contact angle, and increases the electrolyte absorption rate of the separator, thereby enhancing electrolyte retention and ion conductivity. Simultaneously, the adhesive layer utilizes the synergistic effect of PVDF and PMMA to form a high-modulus network structure, effectively suppressing the rebound stress of the base membrane, ensuring tight contact at the cell interface, preventing thermal cracking, and extending the battery's cycle life. Therefore, by controlling the ratio of PVDF and PMMA in the adhesive layer, the thermal stability, electrolyte wettability, and mechanical strength of the composite separator can be balanced. This makes the composite separator provided in this application suitable for sodium-ion batteries requiring long cycle life, and it is cost-effective, which is beneficial for the industrial production of sodium-ion batteries.
[0038] Specifically, in this application, the mass ratio of PVDF to PMMA is any value from 90:10, 85:15, 80:20, 75:25, 70:30, 65:35, and 60:40, or any range between any two ratios. A suitable ratio of PVDF to PMMA in the adhesive layer can balance the thermal stability, electrolyte wettability, and mechanical strength of the composite separator.
[0039] In some embodiments, the base film includes a first PP layer, a PE layer, and a second PP layer; wherein the total thickness of the base film is 12μm to 20μm, and the thickness of the PE layer accounts for 30% to 40% of the total thickness of the base film.
[0040] It should be noted that the thickness of the first PP layer and the second PP layer can be the same or different, preferably the thickness of the first PP layer and the second PP layer is the same.
[0041] The sequential stacking of the base membrane gives the separator higher thermal stability and mechanical strength, and the appropriate total thickness of the base membrane gives the separator better ionic conductivity.
[0042] Specifically, the total thickness of the base film is any value or a range between 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, and 20μm; the thickness of the PE layer accounts for any value or a range between 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, and 40% of the total thickness of the base film.
[0043] In some embodiments, the porosity of the base membrane is 40% to 50% to improve the electrolyte permeability in the composite membrane and make the membrane structure more stable. Specifically, the porosity of the base membrane is any value or a range between 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, and 50%.
[0044] In some embodiments, the adhesive layer thickness is 3μm to 5μm to ensure a more suitable thickness, thereby enabling the composite membrane to possess both superior ion transport and wettability properties. Specifically, the adhesive layer thickness is any value among 3μm, 3.5μm, 4μm, 4.5μm, and 5μm, or a range between any two.
[0045] In a second typical embodiment of this application, a method for preparing a composite diaphragm is provided, the method comprising:
[0046] Step S1: Disperse PVDF and PMMA in an organic solvent to form a gel; wherein the mass ratio of PVDF to PMMA is (90~60):(10~40).
[0047] Step S2: Provide a base film, apply the adhesive solution to one side of the base film, dry to remove the organic solvent, and obtain a composite membrane with the adhesive layer attached to one side of the base film.
[0048] This application provides a method for preparing a composite separator, wherein the mass ratio of PVDF (polyvinylidene fluoride) and PMMA (polymethyl methacrylate) in an organic solvent is adjusted to form a suitable adhesive solution. This adhesive solution is then coated onto one side of a base membrane, and after drying, an adhesive layer is formed. This adhesive layer adheres to the surface of the base membrane, thereby obtaining the composite separator. PVDF is widely used in battery separators due to its electrochemical stability and adhesion, while PMMA is known for its good polarity and wettability. When the mass ratio of PVDF to PMMA is controlled between (90~60):(10~40), the two mix in the adhesive solution to form a synergistic effect, which not only improves the thermal stability of the separator but also enhances the wettability of the separator to the electrolyte, effectively increasing the liquid absorption rate and thus improving the ionic conductivity, ensuring good electrochemical performance of the battery. During hot pressing, the synergistic effect of PVDF and PMMA in the adhesive layer can effectively resist the rebound phenomenon, prevent the composite separator from opening, and thus help maintain tight contact inside the cell, significantly extending the cycle life of the battery. Furthermore, using a combination of PVDF and PMMA as the adhesive layer can optimize the physical and chemical properties of the composite separator, making it more suitable for the harsh environment of sodium-ion batteries, thereby achieving the goal of low-cost, long-cycle battery applications. In short, the composite separator preparation method of this application, through the rational ratio of PVDF and PMMA to form an adhesive layer, results in a composite separator with superior thermal stability, wettability, and cycle life.
[0049] In some specific embodiments, the mass ratio of PVDF to PMMA is any value among 90:10, 80:20, 70:30, 60:40, or any range between the two.
[0050] In order to improve the coating efficiency of the adhesive, in some embodiments, the solid content of the adhesive is any value or a range between 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, and 20%.
[0051] In order to better disperse PVDF and PMMA in organic solvents, in some specific embodiments, the organic solvent is selected from N-methylpyrrolidone.
[0052] In some embodiments, in step S2, the adhesive is applied to one side of the base membrane by spraying, and the drying temperature in step S2 is 30~120℃. The spraying method used in this application to apply the adhesive to one side of the base membrane, compared to traditional coating methods, allows for a more uniform distribution of the adhesive, forming a denser and more uniform adhesive layer. This is more conducive to enhancing the thermal stability and electrolyte wettability of the separator, thereby improving electrochemical performance. A suitable drying temperature is more conducive to rapid curing of the adhesive layer, avoiding excessively high drying temperatures that could damage the base membrane structure, or excessively low drying temperatures that would reduce drying efficiency.
[0053] Specifically, the drying temperature is any value or a range between 30℃, 40℃, 50℃, 60℃, 70℃, 80℃, 90℃, 100℃, 110℃, and 120℃.
[0054] The base film in step S2 above can be obtained commercially or prepared according to the following method. In some embodiments, the preparation method of the base film includes:
[0055] Step A1: The first PP masterbatch, PE masterbatch and second PP masterbatch are co-extruded and cast to form a three-layer composite film; wherein, in the three-layer composite film, the first PP layer, PE layer and second PP layer are stacked sequentially.
[0056] Step A2: Simultaneously biaxially stretch and shape the three-layer composite film to obtain the base film.
[0057] The method for preparing the base membrane provided in this application uses a composite membrane with a three-layer structure of PP / PE / PP as the base membrane. The first PP layer, the PE layer, and the second PP layer are sequentially stacked, and the three-layer composite membrane is formed by co-extrusion and casting. The three-layer composite membrane is then simultaneously biaxially stretched and shaped to obtain the base membrane. This preparation method allows the base membrane to maintain excellent oxidation resistance and thermal stability using the PP layer, while also maintaining good wettability using the PE layer, effectively enhancing the overall performance of the composite membrane.
[0058] In some embodiments, biaxial stretching and setting includes sequential longitudinal stretching, transverse stretching, and heat setting; wherein: the preheating temperature for longitudinal stretching is 125~135℃, the longitudinal stretching temperature is 125~140℃, and the longitudinal stretching ratio is 4~5 times; the preheating temperature for transverse stretching is 125~135℃, the transverse stretching temperature is 125~145℃, and the transverse stretching ratio is 4~5 times; the heat setting temperature is 150~160℃, and the heat setting relaxation rate is 2%~5%. This application, by controlling the preheating temperature, stretching temperature, stretching ratio, heat setting temperature, and relaxation rate of longitudinal and transverse stretching, enables the base film, after biaxial stretching, to maintain the high oxidation resistance and thermal stability of the PP layer while fully utilizing the thermal shut-off characteristics of the PE layer, achieving a stable porosity of 45%±5%, significantly enhancing electrolyte wettability, reducing thermal shrinkage, and improving the stability of the composite membrane under high-temperature environments.
[0059] Specifically, the preheating temperature for longitudinal stretching is any value or a range between any two of 125℃, 126℃, 127℃, 128℃, 129℃, 130℃, 131℃, 132℃, 133℃, 134℃, and 135℃; the longitudinal stretching temperature is any value or a range between any two of 125℃, 128℃, 130℃, 132℃, 135℃, 138℃, and 140℃; and the longitudinal stretching multiple is any value or a range between any two of 4 times, 4.2 times, 4.4 times, 4.6 times, 4.8 times, and 5 times.
[0060] The preheating temperature for transverse stretching is any value or a range between any two of 125℃, 126℃, 127℃, 128℃, 129℃, 130℃, 131℃, 132℃, 133℃, 134℃, and 135℃; the transverse stretching temperature is any value or a range between any two of 125℃, 128℃, 130℃, 132℃, 135℃, 138℃, and 140℃; and the transverse stretching ratio is any value or a range between any two of 4 times, 4.2 times, 4.4 times, 4.6 times, 4.8 times, and 5 times.
[0061] The heat setting temperature is any value or a range between any two of 150℃, 151℃, 152℃, 153℃, 154℃, 155℃, 158℃, and 160℃; the relaxation rate of the heat setting is any value or a range between any two of 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, and 5%.
[0062] In a third typical embodiment of this application, a sodium-ion battery is provided, which includes a separator, wherein the separator is a composite separator provided in the first typical embodiment, or a composite separator prepared according to the second typical embodiment.
[0063] The sodium-ion battery provided in this application uses a composite separator with an adhesive layer coated on a base film. The PVDF and PMMA in the adhesive layer work synergistically to improve the insufficient modulus of pure PVDF adhesive layers after hot pressing. By introducing PMMA and PVDF to form a rigid network structure, not only is the polarity of the adhesive layer increased and the wettability of the electrolyte improved, but the springback effect of the base film is also effectively suppressed during hot pressing, ensuring tight contact at the battery cell interface and thus significantly improving the battery's cycle life. Therefore, the sodium-ion battery provided in this application possesses excellent thermal stability, wettability, and cycle life. Furthermore, due to the use of a low-cost composite separator, it is suitable for large-scale industrial production and shows broad application prospects in energy storage systems and low-speed electric vehicles.
[0064] In some embodiments, the sodium-ion battery further includes a positive electrode and a negative electrode, wherein the positive electrode includes a positive active material, preferably Na. 0.98 Ni 0.33 Fe 0.33 Mn 0.33 O2; The negative electrode sheet includes a negative electrode active material, which is preferably hard carbon.
[0065] In this application, layered oxides are used as the positive electrode active material and hard carbon is used as the negative electrode active material. Together with the composite separator, they further optimize the battery performance.
[0066] The sodium-ion battery provided in this application has excellent thermal stability, electrolyte wettability, and cycle life, and is low in cost, thus having broad application prospects.
[0067] The beneficial effects of this application will be further illustrated below with reference to embodiments and comparative examples.
[0068] Example 1
[0069] This embodiment provides a composite membrane, which includes a base membrane and an adhesive layer coated on one side of the base membrane. The adhesive layer has a thickness of 3 μm and is made of PVDF and PMMA in a mass ratio of 90:10. The base membrane is composed of a first PP layer, a PE layer, and a second PP layer. The total thickness of the base membrane is 15 μm and the porosity is 45%. The thicknesses of the first PP layer and the second PP layer are 5 μm and the thickness of the PE layer is 5 μm.
[0070] The composite membrane was prepared according to the following steps:
[0071] (1) A three-layer composite film is formed by co-extrusion and casting of the first PP masterbatch, PE masterbatch, and second PP masterbatch. The three-layer composite film is then subjected to longitudinal stretching, transverse stretching, and heat setting treatment to obtain a base film with a porosity of 45%. The preheating temperature for longitudinal stretching is 130℃, the longitudinal stretching temperature is 135℃, and the longitudinal stretching ratio is 4.5 times. The preheating temperature for transverse stretching is 130℃, the transverse stretching temperature is 135℃, the transverse stretching ratio is 4.5 times, the heat setting temperature is 155℃, and the heat setting relaxation rate is 4%.
[0072] (2) PVDF and PMMA are dispersed in N-methylpyrrolidone at a mass ratio of 90:10 to prepare a glue solution with a solid content of 15%. The glue solution is sprayed onto the surface of one side of the base film to obtain a composite membrane to be dried. The composite membrane to be dried is dried at 100°C to remove N-methylpyrrolidone to obtain a composite membrane. The thickness of the glue layer after drying is 3 μm.
[0073] Example 2
[0074] The only difference between this embodiment and Embodiment 1 is that the total thickness of the base film is 12 μm, wherein the thicknesses of the first PP layer and the second PP layer are 3.75 μm and the thickness of the PE layer is 4.5 μm.
[0075] Example 3
[0076] The only difference between this embodiment and Embodiment 1 is that the total thickness of the base film is 20 μm, wherein the thicknesses of the first PP layer and the second PP layer are 7 μm and the thickness of the PE layer is 6 μm.
[0077] Example 4
[0078] The only difference between this embodiment and Example 1 is that the mass ratio of PVDF to PMMA in the adhesive layer is 60:40.
[0079] Example 5
[0080] The only difference between this embodiment and Example 1 is that the mass ratio of PVDF to PMMA in the adhesive layer is 80:20.
[0081] Example 6
[0082] The only difference between this embodiment and Embodiment 1 is that the porosity of the base membrane is 40%.
[0083] Example 7
[0084] The only difference between this embodiment and Embodiment 1 is that the porosity of the base membrane is 50%.
[0085] Example 8
[0086] The only difference between this embodiment and Embodiment 1 is that the porosity of the base membrane is 35%.
[0087] Example 9
[0088] The only difference between this embodiment and Embodiment 1 is that the porosity of the base membrane is 60%.
[0089] Example 10
[0090] The only difference between this embodiment and Embodiment 1 is that the thickness of the adhesive layer is 5 μm.
[0091] Example 11
[0092] The only difference between this embodiment and Embodiment 1 is that the thickness of the adhesive layer is 2 μm.
[0093] Example 12
[0094] The only difference between this embodiment and Example 1 is that the thickness of the adhesive layer is 8 μm.
[0095] Example 13
[0096] The only difference between this embodiment and Example 1 is that the mass ratio of PVDF to PMMA in the adhesive layer is 95:5.
[0097] Example 14
[0098] The only difference between this embodiment and Example 1 is that the mass ratio of PVDF to PMMA in the adhesive layer is 55:45.
[0099] Example 15
[0100] The only difference between this embodiment and Embodiment 1 is that the total thickness of the base film is 10 μm; wherein the thicknesses of the first PP layer and the second PP layer are 3.25 μm and the thickness of the PE layer is 3.5 μm.
[0101] Example 16
[0102] The only difference between this embodiment and Embodiment 1 is that the total thickness of the base film is 25 μm; wherein the thicknesses of the first PP layer and the second PP layer are 8.5 μm and the thickness of the PE layer is 8 μm.
[0103] Example 17
[0104] The only difference between this embodiment and Embodiment 1 is that the base film is made of PP film with a thickness of 15μm and a porosity of 45%.
[0105] Comparative Example 1
[0106] The difference between this comparative example and Example 1 is that a base film is used as the separator, and no adhesive layer is coated on the base film.
[0107] Comparative Example 2
[0108] The difference between this comparative example and Example 1 is that the adhesive layer is made of PVDF and no PMMA is added.
[0109] Comparative Example 3
[0110] The difference between this comparative example and Example 1 is that the adhesive layer is made of PMMA and no PVDF is added.
[0111] Experimental Example 1
[0112] (a) The heat shrinkage rate, washing liquid rate and ionic conductivity of the diaphragm provided in the above embodiments were tested respectively. The test results are shown in Table 1 below.
[0113] (1) Test method for heat shrinkage rate: Refer to the national standard GB / T 36363-2018. Cut the diaphragm into 100mm×100mm samples, place them freely in an oven at 150℃ for 1 hour, and then measure and calculate their dimensional changes.
[0114] (2) Liquid absorption rate test method: The gravimetric method is used. After vacuum drying the diaphragm at 80°C for 12 hours, weigh it (G0). Then, immerse it in the electrolyte in an argon glove box for 24 hours until saturation. After taking it out and quickly wiping off the surface droplets, weigh it (G). Calculate the liquid absorption rate (%) according to the formula, where the liquid absorption rate (%) = [(G-G0) / G0] × 100%.
[0115] (3) Ionic conductivity test method: The test shall be conducted in accordance with the multilayer stacking method combined with AC impedance spectroscopy as specified in Clause 6.6.2 of GB / T 36363-2018 "Polyolefin Separators for Lithium-ion Batteries". The test steps are as follows:
[0116] (3.1) Dry the diaphragm under vacuum at 80°C for 12 hours and cut it to the size that matches the blocking electrode.
[0117] (3.2) In an argon glove box, immerse the 1st, 2nd, 3rd and 4th layers of diaphragm in the electrolyte for 2 hours to allow them to fully absorb the electrolyte.
[0118] (3.3) The impregnated membranes of each layer are sandwiched between two stainless steel blocking electrodes to form a symmetrical simulated battery.
[0119] (3.4) At 25°C, the AC impedance of each simulated cell was tested using an electrochemical workstation, with a frequency range of 0.1 Hz to 1 MHz and an amplitude of 5 mV. The intersection points of the high-frequency region and the real axis were read from the Nyquist plot and denoted as R1, R2, R3, and R4.
[0120] (3.5) Plot the number of diaphragm layers n as the abscissa and the measured resistance R. n Perform a linear fit on the ordinate, and the slope of the fitted line is the ion resistance R0 of the single-layer membrane (R² ≥ 0.99 is required).
[0121] (3.6) Measure the thickness d (cm) of the single-layer diaphragm and the effective contact area A (cm²) of the stainless steel blocking electrode, and calculate the ionic conductivity σ according to the following formula: σ=d / (R0×A)
[0122] Where: σ is the ionic conductivity (S / cm), d is the membrane thickness (cm), R0 is the ionic resistance of the monolayer membrane (Ω), and A is the effective contact area of the electrode (cm²). At least three parallel samples should be tested for each sample, and the average value should be taken.
[0123] (ii) Assemble the separators provided in the above embodiments and comparative examples into sodium-ion batteries and conduct a 1000-cycle charge-discharge performance test.
[0124] The assembly steps of a sodium-ion battery include:
[0125] (1) Preparation of positive electrode sheet
[0126] A positive electrode active material, a conductive agent, PVDF, and N-methylpyrrolidone are mixed to obtain a positive electrode slurry, wherein the positive electrode active material is a layered oxide with the chemical formula Na. 0.98 Ni 0.33 Fe 0.33 Mn 0.33 O2, conductive agent is conductive carbon black (SP); the above positive electrode slurry is coated onto the positive electrode current collector and dried in an oven at 90°C to obtain the positive electrode sheet, wherein the positive electrode current collector is an Al foil with a thickness of 12μm.
[0127] (2) Preparation of negative electrode sheet
[0128] The negative electrode active material, conductive agent, styrene-butadiene rubber, and sodium carboxymethyl cellulose were mixed evenly in water at a mass ratio of 94:2:2.5:1.5 to obtain a negative electrode slurry. The negative electrode active material was hard carbon (Zhongke Xingcheng H30-B2), and the conductive agent was conductive carbon black. The slurry was then coated onto the negative electrode current collector and dried in an oven at 90°C to obtain a negative electrode sheet. The negative electrode current collector was an Al foil with a thickness of 12 μm.
[0129] (3) Battery assembly
[0130] The positive electrode, separator, and negative electrode are stacked together in that order, with the negative electrode active material layer extending 2mm beyond the positive electrode active material layer on all sides, and the separator extending 2mm beyond the negative electrode active material layer on all sides, and encapsulated with an aluminum-plastic film.
[0131] (4) Battery baking and electrolyte filling
[0132] The packaged sodium-ion batteries were baked in an oven at 90°C until the moisture content in the sodium-ion batteries was less than 200 ppm. Then, electrolyte was injected at an injection coefficient of 4 g / Ah and the batteries were soaked for 36 hours.
[0133] The assembled sodium-ion battery was subjected to cyclic charge-discharge performance testing. The specific method for testing the cyclic performance of 1000 charge-discharge cycles is as described in GB / T 44265-2025.
[0134] The test results are shown in Table 1.
[0135] Table 1
[0136]
[0137] Note: Since there is no adhesive layer in Comparative Example 1, it is not applicable for evaluating the hot-pressed opening.
[0138] As can be seen from Examples 1-17 and Comparative Examples 1-3, sodium-ion batteries assembled using only the base film as the separator, without a coating layer or with only PVDF or PMMA as the separator, exhibit high thermal shrinkage, low liquid absorption, poor ionic conductivity, and open or severely open after hot pressing, resulting in poor capacity retention after 1000 cycles. It can be seen that the composite separator provided in this application, with PVDF and PMMA in the coating layer working synergistically to form a network structure with high modulus, not only enables the coating layer to bond tightly to the base film, enhancing the structural stability and mechanical strength of the composite separator and improving thermal stability, but also improves the wettability of the composite separator with the electrolyte, reduces the contact angle, increases the liquid absorption rate of the composite separator to the electrolyte, and improves ion transport efficiency. In Comparative Example 3, the coating layer contains only PMMA, which has relatively good hydrophilicity, but its mechanical strength and resilience are insufficient, making it difficult to meet the requirements for separator use in sodium-ion batteries. The slight opening in Example 4 was due to the high proportion of PMMA (40%), which reduced the modulus of the adhesive layer and weakened the resilience, resulting in slight opening. The slight opening caused micro-voids at the interface, uneven current distribution, and increased local polarization. However, the improvement in liquid absorption rate and conductivity partially compensated for the interface defects caused by the "slight opening". Therefore, the capacity retention rate of Example 4 was 88%, which was lower than that of Example 1 (92%), but still significantly better than that of Comparative Example 2.
[0139] As can be seen from Examples 1-7, 10 and 8-9, the appropriate porosity of the base membrane in Examples 1-7 and 10 can help improve the electrolyte permeability in the composite membrane and make the membrane structure more stable, thereby improving the wettability of the composite membrane and the electrolyte, reducing the contact angle, increasing the electrolyte absorption rate of the composite membrane, and improving the ion transport efficiency.
[0140] As can be seen from Examples 1-7, 10 and 11-12, the appropriate adhesive layer thickness in Examples 1-7 and 10 can enable the composite membrane to have better ionic conductivity, thereby improving ion transport efficiency and making the sodium ion capacity retention rate high after 1000 cycles.
[0141] As can be seen from Examples 1-7, 10, and 13-14, the appropriate mass ratio of PVDF to PMMA in the adhesive layer of Examples 1-7 and 10 can further enable PVDF and PMMA to work synergistically, improve the thermal stability of the composite membrane, enhance the wettability of the composite membrane to the electrolyte, effectively increase the liquid absorption rate, and thus improve the ionic conductivity, ensuring good electrochemical performance of the sodium-ion battery.
[0142] As can be seen from Examples 1-7, 10, and 15-16, the appropriate total thickness of the base film and the thickness of the first PP layer and the second PP layer in Examples 1-7 and 10, as well as the thickness of the PE layer, enable the composite separator to have better ionic conductivity, thereby improving the ionic conductivity and ensuring good electrochemical performance of the sodium-ion battery.
[0143] As can be seen from Examples 1-7, 10, and 17, the base membranes in Examples 1-7 and 10 can maintain excellent antioxidant properties and thermal stability using the PP layer, while also maintaining good wettability using the PE layer, effectively enhancing the overall performance of the composite membrane. If only PP membrane is used as the base membrane, the liquid absorption effect is poor.
[0144] As can be seen from the above description, the embodiments of this application achieve the following technical effects:
[0145] This application provides a composite separator, comprising a base membrane and an adhesive layer coated on one side of the base membrane. The adhesive layer material includes PVDF and PMMA, and the mass ratio of PVDF to PMMA is (90~60):(10~40). By utilizing the synergistic interaction of PVDF and PMMA in the adhesive layer to form a network structure with high modulus, not only can the adhesive layer be tightly bonded to the base membrane, enhancing the structural stability and mechanical strength of the composite separator and improving thermal stability, but it can also improve the wettability of the composite separator with the electrolyte, reduce the contact angle, increase the electrolyte absorption rate of the composite separator, and improve ion transport efficiency.
[0146] Furthermore, the composite separator provided in this application utilizes the high-modulus network structure formed by PVDF and PMMA in the adhesive layer to effectively suppress the rebound stress of the base film during hot pressing, ensuring tight contact at the cell interface, preventing hot pressing opening, and thus extending the cycle life of the battery.
[0147] Therefore, by adjusting the mass ratio of PVDF and PMMA in the adhesive layer, the thermal stability, electrolyte wettability, and mechanical strength of the composite separator can be balanced, making the composite separator of this application suitable for sodium-ion batteries that require long cycle life, and it is also inexpensive, which is beneficial to the industrial production of sodium-ion batteries.
[0148] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A composite diaphragm, characterized in that, The composite membrane includes a base membrane, and an adhesive layer is coated on one side of the base membrane. The adhesive layer is made of PVDF and PMMA, and the mass ratio of the two is (90~60):(10~40).
2. The composite diaphragm according to claim 1, characterized in that, The base film comprises a first PP layer, a PE layer, and a second PP layer stacked sequentially. The total thickness of the base film is 12μm to 20μm, and the thickness of the PE layer accounts for 30% to 40% of the total thickness of the base film. And / or, the porosity of the base membrane is 40%~50%.
3. The composite diaphragm according to claim 1 or 2, characterized in that, The thickness of the adhesive layer is 3μm to 5μm.
4. A method for preparing a composite diaphragm, characterized in that, The preparation method includes: Step S1: Disperse PVDF and PMMA in an organic solvent to form a gel; wherein the mass ratio of PVDF to PMMA is (90~60):(10~40). Step S2: Provide a base film, apply the adhesive solution to one side of the base film, dry to remove the organic solvent, and obtain a composite membrane with the adhesive layer attached to one side of the base film.
5. The preparation method according to claim 4, characterized in that, In step S1, the solid content of the adhesive solution is 10%~20%; And / or, the organic solvent is N-methylpyrrolidone.
6. The preparation method according to claim 4, characterized in that, In step S2, the adhesive is applied to one side of the base film by spraying. And / or, the drying temperature is 30~120℃.
7. The preparation method according to any one of claims 4 to 6, characterized in that, In step S2, the method for preparing the base film includes: Step A1: The first PP masterbatch, PE masterbatch, and second PP masterbatch are co-extruded and cast to form a three-layer composite film; wherein, in the three-layer composite film, the first PP layer, PE layer, and second PP layer are stacked sequentially. Step A2: The three-layer composite film is simultaneously biaxially stretched and shaped to obtain the base film.
8. The preparation method according to claim 7, characterized in that, Step A2, the biaxial stretching and setting, includes: longitudinal stretching, transverse stretching, and heat setting performed sequentially; wherein: the preheating temperature for longitudinal stretching is 125~135℃, the longitudinal stretching temperature is 125~140℃, and the longitudinal stretching ratio is 4~5 times; the preheating temperature for transverse stretching is 125~135℃, the transverse stretching temperature is 125~145℃, and the transverse stretching ratio is 4~5 times; the heat setting temperature is 150~160℃, and the relaxation rate of heat setting is 2%~5%.
9. A sodium-ion battery, characterized in that, The sodium-ion battery includes a separator, which is a composite separator according to any one of claims 1 to 3 or a composite separator obtained by the preparation method according to any one of claims 4 to 8.
10. The sodium-ion battery according to claim 9, characterized in that, The sodium-ion battery further includes a positive electrode and a negative electrode, wherein the positive electrode includes a positive active material, preferably Na+. 0.98 Ni 0.33 Fe 0.33 Mn 0.33 O2; the negative electrode sheet includes a negative electrode active material, preferably hard carbon.